A new damsel-dragonfly from the Lower Jurassic of northwestern China and its paleobiogeographic significance. (27th July 2016) - Zheng, Daran; Nel, André; Wang, Bo; Jarzembowski, Edmund A.; Chang, Su-Chin; Zhang, Haichun
Abstract: A new species of the Lower Jurassic genus Dorsettia Whalley, 1985 is described from the Lower Jurassic Badaowan Formation of the Junggar Basin, northwestern China, as Dorsettia sinica new species. It provides additional morphological characters for this genus and is the earliest Jurassic dragonfly in China after the end-Triassic extinction. The occurrence of Dorsettia in England and northwestern China indicates that the end-Triassic extinction probably did not have a drastic influence on damsel-dragonflies, or that the dispersal of damsel-dragonflies was relatively quick during the earliest Jurassic.